(untitled) (BIRDEM Medical Journal, 2018)
Background: Circumcision is a widely performed surgical procedure. Though it is a simple operation, oftentimes a number of complications are encountered. Among them post-circumcision pain and bleeding are of paramount concern. These may cause apprehension in the parents as well as in patients. Surgical procedure of circumcision should, therefore, be pain-free and devoid of complication as much as possible. Methods: In this prospective randomized doubnle blind observational study, we had compared two commonly practiced technique of circumcision and evaluated the outcomes in regard to post circumcision pain and complications, and overall cosmesis. The study was carried out in 100 boys randomly allocated in two groups from July 2016 through June 2017. Result: The results revealed that the modified sleeve method in which the frenular artery of penis was preserved was associated with significantly less post circumcision pain and fewer complications. In addition, boys who underwent modified sleeve method exhibited better overall cosmesis. Conclusion: It could be reasonably inferred that preservation of frenular artery during circumcision reduces post circumcision pain and complications and provides better cosmesis. Birdem Med J 2018; 8(2): 145-150